A problemática da salinização do solo no perímetro irrigado de São Gonçalo - PB - Silva Neto, Manoel Faustino da (2013)
Salinization appears as one of the main present problems in semiarid irrigated areas of the Northeast Region, leading to environmental and economic losses. This study consisted of a degradation analysis of natural resources and the impacts brought up by inadequate soil use in the São Gonçalo Irrigated Perimeter. In order to analyze this problem, the following methodological procedures were carried out: map elaboration for soil use; field research with collection samples of water (6 samples), and of soil (157 samples) for a laboratorial analysis, and questionnaires in a universe of 100 colonists for a secondary data collection. Results found showed that: the Perimeter is, mostly, made up of soils with a great salinization tendency; many pieces of land are cultivated with well-water with high concentrations of salt in solution; the flooding irrigation method is one of the irrigation types used, also contributing for local salinization: plantations with the most remarkable PISG production are of a vegetal type which have high productive levels even in salinization (coconut and rice); many spaces are abandoned or utilized for cattle-raising because they do not offer any agricultural productivity conditions any longer; most of the irrigators have salinization problems in their allotments; 51,78% of the PISG territory have high salinity levels, making it difficult for agriculture to develop with species that are not adapted to such conditions; a considerable part of the irrigators appear to be unaware of what motivates the problem of salinization and do not know the fact that the irrigation methods and the water utilized creates or intensifies this process; most of the irrigators do not have technical maintenance, making the cultivation without the technical knowledge demanded by irrigated agriculture; there is great dissatisfaction by the irrigators towards the present situation of the Perimeter s infrastructure, and problems about roads and the occurrences of obstructions in drainage and irrigation channels were the main complaints. Based on what was observed, we believe that, although benefits able to be obtained by the use of irrigated agriculture are incontestable, it is also undeniable that they may bring remarkable impacts over the environment. Taking into account that the reality observed in PISG is part of many of the perimeters irrigated in the Brazilian semiarid, a sense of reflection over these areas as well as the present activity arouse.